The Transformation of Ideology in The Social Life Processes of The New Uzbekistan - Shokrukh Ismatov Murod Ugli (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The extensive reforms being implemented in the New Uzbekistan are aimed at ensuring the priority of spiritual factors in all areas of social life. As we know, today there is intense struggle and competition in the world, and conflicts of interest are escalating. The processes of globalization are bringing unexpected problems along with immeasurable new opportunities for humanity. Threats and dangers to national identity and spiritual values are increasingly on the rise. A self-centered mindset, a casual attitude toward work and family, and a consumerist mentality are being subtly instilled in people’s minds, especially among the youth, through various means. The ideology of the New Uzbekistan that we are creating will be based on the principles of goodness, humanity, and humanism. By ideology, we primarily understand the education of thought and the cultivation of national and universal values. These are based on the centuries-old life understanding and values of our people, as emphasized by our president, Shavkat Mirziyoyev.